Knowledge transfer: a case study approach - Tichá, Ivana; Havlícek, Jaroslav (Applied Studies in Agribusiness and Commerce, 2008)
The article builds on the growing importance of knowledge as a strategic resource for maintaining the competitive advantage of a business. We illustrate one of the initiatives contributing to effective knowledge transfer by describing a case study approach which suggests how universities might assist in disseminating knowledge and enhancing industry competitiveness.The case study approach is apparently an effective way to share best practices, and with the use of appropriate ICT tools, it provides for an enormous diffusion of codified (explicit) knowledge in the industry.The example in the focus of this article describes aVirtual Portal designed as a single-point access to information and tools (case studies, decision models and software), with the emphasis on case studies (their selection, coding and use).